Report on District Planning Status and Way Forward September, 2008 - Planning Commission (Planning Commission Government of India, 2008)
The 2008 Report on District Planning in India, commissioned by the Planning Commission, evaluates the status, effectiveness, and challenges of district planning across Indian states. Covering 626 districts, the report identifies the limited functionality of District Planning Committees (DPCs) and emphasizes the need for stronger participatory governance. Best practices from states like Kerala, Karnataka, Andhra Pradesh, Nagaland, and Punjab demonstrate successful strategies in community engagement, decentralized planning, and service delivery. The report also highlights the role of Technical Support Institutions (TSIs) such as NABARD, IRMA, CRRID, and NIRD in facilitating resource mapping, project proposal development, and capacity building. A structured manual for district planning is proposed, emphasizing visioning, resource mapping, monitoring, and evaluation, with a participatory approach at village, block, and district levels. The report advocates integrated rural-urban planning, community-driven microplanning, and robust monitoring to enhance transparency, accountability, and development outcomes across India.
Government of India Planning Commission
Keywords: District Planning; Microplanning; District Planning Committee; Community Participation; Resource Mapping; Technical Support Institutions; Rural Development; Urban Planning; Thematic Consolidation; Monitoring And Evaluation; Participatory Governance; Development Initiatives